Postmortem diagnosis of sitosterolaemia by next-generation sequencing in a patient with severe hypercholesterolaemia and cardiovascular failure. (2019) - Qiao, Yun; Xu, Minjie; Yan, Zheng; Liu, Qiang; Chen, Wanjun; Xiong, Jianfei; Zhu, Changqing; Lu, Xiaoye
Abstract: Background and aims: Sitosterolaemia (STSL; OMIN #210250) is a disorder of lipid metabolism and a rare autosomal recessive condition caused by loss-of-function biallelic mutations in the adenosine triphosphate-binding cassette, subfamily G member 5 ( ABCG5 ) gene (NM_022, 436.2) or in the adjacent ABCG8 gene (NM_022, 437.2). STSL patients often have high plasma total sterols and present a heterogeneous phenotype. Here, we describe a male patient with a post-mortem diagnosis of STSL who was admitted to the emergency department with advanced heart failure, tendon xanthomas and findings from the follow up with his living family members. Methods: We established a family pedigree and performed whole-exome next-generation sequencing for the patient and Sanger sequencing of DNA samples obtained from his living family members. Plasma sterol (β-sitosterol) level was measured by gas chromatography/mass spectrometry. Results: Both the patient and his younger brother carried a homozygous mutation of p. R263Q (c.788G > A) in the ABCG8 gene. The patient's plasma plant sterol level was extremely high (β-sitosterol: 107.5 μg/ml), and the plasma β-sitosterol level of his younger brother without tendon xanthomas was also abnormally high (51.5 μg/ml). The β-sitoserol levels of other living family members including ones with a heterozygous mutation of p. R263Q (c.788G > A) were normal (i.e. undetectable). Based on the results of genetic detection and very high plasma level of β-sitosterol, we made a definitive diagnosis of STSL. Conclusions: Emergency physicians should be aware of the need to further investigate individuals with xanthomas and cardiovascular disease using biochemical and genetic analyses to aid in diagnosis and intervention. Graphical abstract: Image 1